2020
DOI: 10.3390/biology9080190
|View full text |Cite
|
Sign up to set email alerts
|

Interplay among ATP-Dependent Chromatin Remodelers Determines Chromatin Organisation in Yeast

Abstract: Cellular DNA is packaged into chromatin, which is composed of regularly-spaced nucleosomes with occasional gaps corresponding to active regulatory elements, such as promoters and enhancers, called nucleosome-depleted regions (NDRs). This chromatin organisation is primarily determined by the activities of a set of ATP-dependent remodeling enzymes that are capable of moving nucleosomes along DNA, or of evicting nucleosomes altogether. In yeast, the nucleosome-spacing enzymes are ISW1 (Imitation SWitch protein 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 146 publications
(246 reference statements)
1
22
0
Order By: Relevance
“…Although we do not know the exact impact of this change on chromatin in our mutants, such a change might affect higher-order chromatin folding, chromatin compaction, and DNA accessibility (Correll et al, 2012; Li et al, 2016),possibly leading to some of the transcriptional defects observed in spt6-YW . Such an increase in inter-nucleosome distances has been observed in several other classes of mutants, including mutations that impair the chromatin remodelers Isw1, Isw2, Ino80, and Chd1 (Prajapati et al, 2020), as well as the Hir complex (Vasseur et al, 2016), a histone chaperone, and Yta7, a chromatin associated protein (Lombardi et al, 2011). Interestingly, we show that inactivation of one of these remodelers, Chd1, rescues spt6-YW and spn1-K192N mutant phenotypes (Table S2).…”
Section: Discussionmentioning
confidence: 83%
“…Although we do not know the exact impact of this change on chromatin in our mutants, such a change might affect higher-order chromatin folding, chromatin compaction, and DNA accessibility (Correll et al, 2012; Li et al, 2016),possibly leading to some of the transcriptional defects observed in spt6-YW . Such an increase in inter-nucleosome distances has been observed in several other classes of mutants, including mutations that impair the chromatin remodelers Isw1, Isw2, Ino80, and Chd1 (Prajapati et al, 2020), as well as the Hir complex (Vasseur et al, 2016), a histone chaperone, and Yta7, a chromatin associated protein (Lombardi et al, 2011). Interestingly, we show that inactivation of one of these remodelers, Chd1, rescues spt6-YW and spn1-K192N mutant phenotypes (Table S2).…”
Section: Discussionmentioning
confidence: 83%
“…Nucleosomes restrict access to DNA and are potent inhibitors of transcription and other DNA-dependent processes in vitro. Cells regulate access to their DNA in part by deploying ATP-dependent chromatin remodeling complexes that are capable of overcoming the nucleosome, either by removing it from the DNA or by sliding it along the DNA 3 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The best-described role for RSC in regulating chromatin architecture and transcriptions is its ability to generate NDRs, by sliding or evicting nucleosomes [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The best-described role for RSC in regulating chromatin architecture and transcriptions is its ability to generate NDRs, by sliding or evicting nucleosomes [2224]. Moving the +1 nucleosome allows for TATA binding protein (TBP) promoter binding and transcription initiation [25].…”
Section: Introductionmentioning
confidence: 99%